Valance Band Maximum and Thermoelectric Properties of Bi\(_2\)O\(_2\)Se: First-Principles Calculations - Tran, Van Quang (Communications in Physics, 2020)
Bi2O2Se has been known as a promising thermoelectric material with low thermal conductivity. Detail understanding of band structure is therefore important. In this report, by employing first-principles density functional theory and using primitive unit cell, the electronic band structure of Bi2O2Se is examined. The compound is found to be a narrow band gap semiconductor with very flat bands at the valence band maximum (VBM). Nevertheless, the curvature of energy surface at VBM is directional dependent. Overall, the heavy bands at VBM do not reduce drastically electrical conductivity. It is demonstrated by utilizing the solution of Boltzmann Transport Equation to compute the transport coefficients, i.e. the Seebeck coefficient, the electrical conductivity thereby the power factor and the electronic thermal conductivity. The figure of merit of the compound is also estimated and discussed. The p-type doping is suggested increasing the thermoelectric performance of the compound. All results are in good agreement with experiments and calculations reported earlier.